Diversity of bird community in Hohhot - Ariunjargal, G; Guisheng, Yang (Mongolian Journal of Agricultural Sciences, 2014)
The article contains research on avifauna compliment, numeral and bird distribution which depend on differentiation of habitat and seasons in Hohhot for last year. A bird is one of the important species of vertebrates which has an essential role on ecological balance and biological control. Having diversity of birds is the main composition of biological diversity. Bird community structure is determined by relationship of bird’s species and general correlation of birds and environment. Diversity of bird community structure has direct correlation of its species, bird community numeral and habitat. Also it depends on geographical factor, habitat, diversity of plant community, plant vertical structure, food resource, possibility of shelter and other factors. Therefore, bird species become a very valuable indicator for ecological condition of the city and environmental ecological quality. We have divided the areas around Hohhot, Inner Mongolia into 6 different habitats such as grassland, farmland, residential area, woodland, wetland and garbage dump. We have performed the bird fundamental study, and investigated bird flora, ecology, distribution, diversity, environment, and community structure in different habitats and seasons. DOI: http://dx.doi.org/10.5564/mjas.v11i2.240 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.159-165